Conformity in Modern Science: An Engine of Societal Transformation? - Natalia Gennadievna Popova; Yan Yurievich Moiseenko; Thomas Alexander Beavitt (Changing Societies & Personalities, 2017)
The penetration of science into all spheres of life has self-evidently become a contemporary “megatrend”. In turn, science itself is also undergoing distinct transformations, e.g., as a result of such processes as increasing regulation and bureaucratisation within academia. In this context, researchers as active producers of scientific knowledge face multiple challenges, including the need to cope with increasing regulation of their everyday practices. Therefore, our research purpose was to investigate the phenomenon of conformity, which, although always having been inseparable from social life, is acquiring a new significance today. Various representations of conformity (e.g. conformist behaviour) have received a great deal of attention from sociologists, biologists and psychologists; however, to our knowledge, there is no generally accepted philosophical understanding of its nature. In this paper, we provide a phenomenological study of conformity on the basis of a comprehensive literature analysis and evaluate its role as a mode of existence in modern science. For the sake of clarity, some illustrations from the everyday lives of researchers are given, including the distribution of the IMRAD format of research articles. Conformity in science is predicted to involve consequences at three distinct levels: (1) within a scientific community, when scientists follow prescribed patterns of conduct; (2) within a particular society when people from all walks of life conform to the standards set by the scientised world-view; and (3) at the global level when non-western communities conform to western standards of life through borrowing western scientific world picture.